2022
DOI: 10.1002/tox.23445
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, rather than neurogenesis, induces significant hippocampal‐dependent learning and memory impairment in chronic low Cd2+ exposure

Abstract: Cadmium (Cd), a ubiquitous toxic heavy metal, with the intractable trait of low degradation, can induce multiple organ damage. Whereas, far less is known about its neurotoxicity and the specific mechanism in the chronic low Cd exposure. To investigate the chronic neurotoxicity of Cd2+, we traced its effects for up to 30 months in mice which were exposed to Cd2+ by drinking the mimicking Cd‐polluted water. We found the toxicity of chronic Cd exposure was a process associated with the transition from autophagy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Li et al designed a chronic cadmium-induced neurotoxicity experiment in mice that lasted 30 months [ 124 ]. They found that the toxicity of chronic cadmium exposure was associated with the transition from autophagy to apoptosis, and the autophagy-apoptosis switch was cadmium dose-dependent, with a threshold of [Cd 2+ ] 0.04 mg/L.…”
Section: The Toxicity Of Cadmium Toward the Kidney Liver Bone And Brainmentioning
confidence: 99%
“…Li et al designed a chronic cadmium-induced neurotoxicity experiment in mice that lasted 30 months [ 124 ]. They found that the toxicity of chronic cadmium exposure was associated with the transition from autophagy to apoptosis, and the autophagy-apoptosis switch was cadmium dose-dependent, with a threshold of [Cd 2+ ] 0.04 mg/L.…”
Section: The Toxicity Of Cadmium Toward the Kidney Liver Bone And Brainmentioning
confidence: 99%
“…Ingestion of contaminated food, water and air is the most direct route of Cd exposure (Filippini et al, 2016). Excessive Cd exposure can lead to damage in various organs, containing liver, kidney, brain, bone, heart and spleen (Chen et al, 2018; Guan et al, 2021; He et al, 2020; Li, Dong, et al, 2022; Suchy‐Dicey et al, 2020; Wang et al, 2022; Zang et al, 2019; Zhao, Li, et al, 2021). Studies have indicated that Cd exposure can induce dysfunction in lysosomal, inhibit autophagy and cause oxidative stress through bromodomain‐containing protein 4 (BRD4), resulting in acute kidney injury (Gong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cd can also induce blood–brain barrier (BBB) dysfunction and enter the brain, leading to neurodegenerative disorders 4 . Numerous studies have shown that the neurotoxic mechanisms of Cd primarily involve oxidative stress, apoptosis, and autophagy 1,5,6 …”
Section: Introductionmentioning
confidence: 99%